Strategy for Optimizing Nazir's Role in Productive Waqf Management in Urban Community Environments - Achmad Fauzan; Erika Amelia; Riris Aisyah Prasetyowati (Universitas of Muhammadiyah Makassar, 2024)
Humans are familiar with the word Waqf as the act of giving productive assets or principal items regardless of personal interference, channeling the results and benefits specifically in accordance with the objectives of the waqf, whether for individual, community, religious or general interests. This research aims to examine the extent of Nazir's strategy in optimizing its role in managing productive waqf assets in urban communities. This research used a qualitative research. The primary data is two Islamic institutions in South Jakarta, one of whose activities is waqf management combined with library research. South Jakarta is considered to represent the lives of urban communities living in the capital. The tools used in this research are SWOT Analysis (Strength, Weakness, Opportunity, Threat) and Thomas L. Saaty's AHP (Analytical Hierarchy Process) which are calculated using Expert ChoiceTM software. This research found that waqf and its development, urban society, information and technology, and management theory to find clarity between the strategies implemented by Nazir towards productive waqf management in urban society. It can be concluded that the both Nazir institution is a professional with the criteria of honesty-trustworthiness-fairness, procedural and emotional-spiritual intelligence agreed upon by both Nazir institutions as the three main aspects that support the role of the Nazir institution in managing waqf assets professionally.